Osteonecrosis of the Jaws in Dogs in Previously Irradiated Fields: 13 Cases (1989–2014) - Nemec, Ana; Arzi, Boaz; Hansen, Katherine; Murphy, Brian G.; Lommer, Milinda J.; Peralta, Santiago; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2015)
The aim of this report is to characterize osteonecrosis of the jaws (ONJ) in previously irradiated fields in dogs that underwent radiotherapy (RT) for oral tumors. Osteoradionecrosis of the jaw (ORNJ) was further defined as osteonecrosis in a previously irradiated field in the absence of a tumor. Thirteen dogs clinically diagnosed with fifteen ONJ lesions were included in this retrospective case series. Medical records were reviewed for: breed, sex, weight, and age of the patient, tumor type, location in the oral cavity and size, location of the ONJ, time from RT to ONJ onset, known duration of the ONJ, and tumor presence. Where available, histological assessment of tissues obtained from the primary tumor, and tissues obtained from the ONJ lesion, was performed, and computed tomographic (CT) images and dental radiographs were reviewed. Radiotherapy and other treatment details were also reviewed. Twelve dogs developed ONJ in the area of the previously irradiated tumor or the jaw closest to the irradiated mucosal tumor. Recurrence of neoplasia was evident at the time of ONJ diagnosis in five dogs. Time from RT start to ONJ onset varied from 2 - 44 months. In three cases, ORNJ developed after dental extractions in the irradiated field. Dental radiographs mostly revealed a moth-eaten pattern of bone loss, CT mostly revealed osteolysis, and histopathology was consistent with osteonecrosis. To conclude, development of ONJ/ORNJ following RT is a rare, but potentially fatal complication. Patients undergoing RT may benefit from a comprehensive oral and dental examination and treatment prior to RT.